1995
DOI: 10.1007/bf00123372
|View full text |Cite
|
Sign up to set email alerts
|

Histological evaluation of xenogeneic bone treated by supercritical CO2 implanted into sheep

Abstract: Untreated xenogeneic bone is known to be rejected when implanted into human or animal bone. It contains bone marrow tissue which is highly antigenic. To be used as an alternative to auto and allografts, this antigenic material must be entirely removed. Removal of this soft tissue contained in the bone structure was performed using a delipidation process with supercritical CO2 followed by a deproteination with hydrogen peroxide or protease extraction. Such prepared materials were implanted into sheep bone for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…The preservation of biomechanical properties by SCCO 2 was corroborated by the non-mechanical characterization of SCCO 2 -treated samples other than the SCCO 2 -1%-SDS group in the present study, reiterating the gentle character of SCCO 2 found by many pilot studies [40,46,59,69,[72][73][74][75][76][77][78][79]. Previously, Antons et al [90] also resorted to SEM for ultrastructural examination and found that the orientation, size, and density of collagen fibers in SCCO 2 -treated tendons and skins were generally comparable to those of the native tendons.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The preservation of biomechanical properties by SCCO 2 was corroborated by the non-mechanical characterization of SCCO 2 -treated samples other than the SCCO 2 -1%-SDS group in the present study, reiterating the gentle character of SCCO 2 found by many pilot studies [40,46,59,69,[72][73][74][75][76][77][78][79]. Previously, Antons et al [90] also resorted to SEM for ultrastructural examination and found that the orientation, size, and density of collagen fibers in SCCO 2 -treated tendons and skins were generally comparable to those of the native tendons.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, decellularization, the process of removing resident cells and nuclear material, has been increasingly recognized as a crucial step in the tissue engineering process to mitigate their SCCO 2 has been demonstrated to inactivate viruses [65][66][67], vegetative bacteria [57,62,68], and, working synergistically with additives such as peracetic acid (PAA) and hydrogen peroxide (H 2 O 2 ), bacterial spores [69,70] to achieve SAL 10 −6 [54,61], though the exact mechanism remains obscure [71]. Pioneering studies have found it to be a gentle agent that appears to preserve the mechanical properties of a variety of tissues such as heart valves [59], lungs matrices [72], amniotic membrane [73], bones [66,[74][75][76][77], acellular dermal matrices [69], and menisci [78], while there is still a paucity of literature on tendons [40,46,79].…”
Section: Introductionmentioning
confidence: 99%
“…The efficient volume of delipidation can be improved by increasing the time spent within the SC.CO . The efficient bone volume for bone marrow deproteination can, as has previously been described be greatly enhanced by dissolution of protease in the SC.CO [12]. It is therefore likely that the treatment of large bone volumes by SCF technology could facilitate their subsequent integration.…”
Section: Discussionmentioning
confidence: 96%
“…20 Hydrogen peroxide (H 2 O 2 ), sodium hydroxide (NaOH), sodium dihydrogen phosphate (NaH 2 PO 4 ), and ethanol have also been utilized for a series of processing to remove partial protein ingredients of sheep bone and decrease the antigenicity. 21 They confirmed that such ovine-derived materials exhibit good biocompatibility and osteoconduction by a series of in vivo tests. [22][23][24] Afterward, they developed a commercial commodity, called OXBONE.…”
Section: Introductionmentioning
confidence: 78%
“…[20][21][22][23][24] This novel bone graft revealed good compatibility. [20][21][22][23][24] However, SCF was utilized only to remove the lipid content of the sheep bone in the Fages et al study, and the other characteristics and advantages of SCF were not be completely utilized, for example, the high permeability and the material processing capability. 17,18 Ethanol is generally added to SCCO 2 as a specific modifier.…”
Section: Discussionmentioning
confidence: 99%